(untitled) (Revista de El Colegio de San Luis, 2018)
This paper aims to critically analyze the structure and the new culture of public administration paradigm named as the new administration or public management of public organizations. The main challenge is to try to explain why the dysfunctional management practices in the structure and the new culture of public organizations that are copied from focusing on administrative processes management practices of private organizations model. In doing so, it has been reviewed the literature in general from the perspective of neo-institutionalism on this subject and by using the method of critical analysis of organizations. More than dysfunctions, in this work the main challenges and worries to the implementation of the paradigm of management or governance are identified. Despite the theoretical -methodological nuances of the new institutional economy and its implications for economic theory, it is inadequate to describe only subtly strategies of the private management. This paper presents an original approach to the critical analysis of new public management. The revision of the paradigm of new public management is carried out essentially in the methodological steps needed to question and identify the action of the state in the administration of organizations and public agencies, by applying the specific management practices, based on the theoretical and methodological framework of the new institutionalism critical criteria.